A critical reflection on the future of intellectual capital: from reporting to disclosure. Issue 1 (11th January 2016) - Dumay, John
Abstract : Purpose: – The purpose of this paper is to offer a personal critical reflection on the future of intellectual capital (IC) based on my experience as an IC researcher, author, editor, teacher and practitioner. Design/methodology/approach: – Offers a first-hand reflection on the future of IC, using evidence collected from IC in the field and the author's personal reflections. Findings: – I argue that the authors need to abandon reporting and instead concentrate on how an organisation discloses what "was previously secret or unknown", so that all stakeholders understand how an organisation takes into consideration ethical, social and environmental impacts in keeping with an eco-systems approach to IC. Research limitations/implications: – While much of the empirical evidence presented in this paper is freely available to all scholars, the interpretation and findings is subjective. Other researchers, given the same opportunity and evidence, may not necessarily make the same conclusions. Social implications: – We are now on the cusp of the fourth stage of IC research (Dumay, 2013), whereby IC expands its boundaries into the wider eco-system, to "go beyond IC reporting" (Edvinsson, 2013, p. 163). Originality/value: – Offers a critical review of the impact of IC reporting which is relevant to consider because of the newfound resurging interest in IC, based on the current push for integrated reporting ( < IR > ), which arguably contains IC information targeted at investors.